Upheaval [compact disc, unabridged] : turning points for nations in crisis - Diamond, Jared M (Recorded Books, Inc., 2019)
Diamond shows how seven countries have survived defining upheavals in the recent past, and he identifies patterns in the way that these distinct nations recovered from calamity.